526 MICROSATELLITE INSTABILITY IN GASTRO-ESOPHAGEAL ADENOCARCINOMAS. (14th September 2020) - Katz, A; Evaristo, G; Issac, M; Ramirez-GraciaLuna, J; Park, M; Camilleri-Broët, S; Marcus, V; Vinh Thai, D; Bailey, S; Sangwan, V; Fiset, P; Bass, A; et al.
Abstract: : Microsatellite instability (MSI) in gastro-esophageal adenocarcinomas (GEAs) is associated with poor response to chemotherapy; however, this association is poorly understood. The aim of this study is to better understand the clinical relevance and mutational landscape of MSI in GEA. Methods: In order to assess the status of mismatch repair (MMR) proteins, we performed immunohistochemistry for MLH1, MSH2, MSH6, PMS2 and BRAF V600E on tissue microarrays constructed from 161 patients with esophageal adenocarcinoma and 65 patients with gastric adenocarcinoma, operated between 2011 to 2019. MMR- deficient (MMR-D) status was confirmed using full sections of tumors. Demographics, tumor, and treatment details, operative variable and overall survival were evaluated. Genomic characterization of 3 MSI-H and 10 MSS patients was performed using deep targeted sequencing of 234 potential oncogenic genes. Statistical analysis was performed using Cox regression, logistic regression, ANOVA or Chi-square tests. Results: Among the 28 (12%) MMR-D immunophenotype patients identified: 25 showed a combined MLH1/PMS2 loss, one case with MSH2/MSH6 loss and two cases with isolated MSH6 or MSH2 loss. Patients in the MMR-D were older (74 ± 14 vs 67 ± 11 years, p = 0.01) and with more Siewert-III and sub-cardia tumors [64%(18) vs 40%(79), p = 0.002] compared to MMR-Stable patients. All other variables including sex, stage and grade were not significantly different. MMR-D immunophenotype was associated with better overall survival (Median survival of 5.7vs2.3 years, p < 0.04) (Figure 1A). Genomic analysis linked patients with D-MMR with a higher mutational burden with some potentially targetable mutations (Figure 1B). Conclusion: The significant proportion of MMR-D immunophenotype identified in this gastroesophageal cohort and the different pattern of overall survival and genetic mutations associated with this phenotype, highlight the importance of further characterization and understanding the mechanisms and role of MMR status in GEAs.